Quo vadis, Folklore Studies? - Voigt, Vilmos (Tautosakos darbai, 2015)
The article presents a problematic survey of journals in folklore, ethnology and anthropology. Starting from the very first publications, launched as early as the end of the 19th century, the author discusses their global panorama and general situation until nowadays, concentrating also on some essential theoretical and interdisciplinary issues in this field of humanities. Particular attention is paid to the journals published in the Eastern Europe (former “Soviet” countries), and especially – in the Baltic countries. Finally, the author concludes that in spite of radical social and cultural changes, many of the journals could survive until nowadays, and that they are necessary and useful. Still, he notes the lack of new “revolutionary” theories and methodologies, and calls for discussing the shape and direction that these periodicals should take.
Keywords: -